История взглядов Герхарда Шредера на социально-экономическое развитие Германии - Umarov, S. Y. (Journal of history, 2023)
This article discusses the views of G. Schröder, who is at the top of the "Red-Green" coalition of the Federal Republic of Germany, in domestic and foreign policy. If we look at any country in the world, we can see that reforms were carried out in the political, social, economic, spiritual and other aspects of the state based on a specific program during the time of each head of the government. We also tried to shed light on the economic and social development of Germany in this article, analyzing the views of G. Schröder, who is at the top of the "Red-Green" coalition of the Federal Republic of Germany, in domestic and foreign policy. Because it is not wrong to say that the German state embodies democratic social principles not only in Europe, but also in the world, has rich experience, and has its place among the countries of the world in all fields.